(3OjhGf GdbGSe Hf Ydi Hf gJjeds - (3GdbGSe Hf Ydj Hf gJjed GdNRGYj Gdjefj GdeNdGaj,J (B656 (3g` s
(3ChdgG (B:s
(3bGd GdYHO GdbGSe Hf Ydi Hf gJjed SCdfi HYV GdSGOI Cf CLeY dg TjFkG eeG SfM Hg GdNGWQ s
(3BNQgG (B:s
(3hBNQg eHJhQ , jfJgi CKfGA bUjOI ai QKGA hdOg SdWGf Hf bGSe , eWdYgG (B: (3CSeYfi aOGc CHj hCei ef GdCShGA dG NGdj hYei s
(3GdfSNI HgG MhGTs
(3OjhGf TYQ eQJH Ydi GdEZQGVs
(3Ydi MhGTjgG HYV GdJUMjMGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B109s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs